The Strategies and Techniques of Addressing the Current Linguistic and Cultural Challenges Facing the Arabic Language - Tamim, Abdel-Hadi M. Omer (Journal of Posthumanism, 2025)
This study aims to investigate and analyse the current linguistic and cultural challenges that face the Arabic Language. The Descriptive Analytical Method is employed since it suits such type of study. The researcher presents the techniques and strategies of Arabiciization, translation, and interpretation to enable Arabic language to accommodate the modern technological terms into it. This study is useful to language planners, educationists, and researchers.